Misbehaviors of Front-Line Research Personnel and the Integrity of Community-Based Research - True, Gala (2011)
There has been little empirical research into misconduct and misbehavior among community research workers who recruit and collect data in vulnerable and marginalized health populations and are also members of those same communities. We conducted qualitative interviews with community research workers and traditional research assistants to understand the context and consequences of misbehaviors that pose a threat to research ethics and data integrity. In our sample, more community research workers acknowledged engaging in research wrongdoing than did traditional research assistants. These behaviors were most prevalent among community research workers who were not well-integrated into the research team. We suggest best practices for investigators to promote an environment that supports research integrity in research projects that employ community research workers.